THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON COMPANY PERFORMANCE (STUDY ON BANKING COMPANIES IN INDONESIA) - RATIH BUDI SETYORINI (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
Corporate social responsibility disclosure on company performance will have an impact on the longterm investment decisions ofstakeholders. This study tested whether CSR disclosure had an influenceon the financial performance and market of banking companies.This study utilized corporate social responsibility disclosure (CSRD) as the independent variable. Reports from 10 companies for four years (2015-2018)that have been listed on the Indonesia Stock Exchange were selected using purposivesample method. Data analysis utilized regression with SPSS 21. The result showed that CSR disclosurehad an influence on the financial performance of banking companies as the financial performancedetermined by Return on Investment (RoI). Meanwhile, CSR disclosure had no influence on companymarket performance, but this was affected by leverage, company size, and company age. This wasbecause stakeholders had difficulties in getting the information needed by companies for decisionmaking and they need to pay attention to the aspectof financial performance.Keywords : Corporate Social Responsibility Disclosure, regression, Return on Investment,stakeholders